2007
DOI: 10.1029/2006ja011945
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of geomagnetic storms depends on the X‐line location in the plasma sheet

Abstract: [1] Magnetic reconnection in the plasma sheet, known as the near-Earth X-line (NEXL), is observed within $30 R E from Earth during substorms. In the absence of substorms, the reconnection X-line is observed beyond $30 R E , denoted as mid-distant-tail X-line (MDXL). During quasi-periodic substorms, convection is enhanced by the NEXL to intensify the ring current of major storms with Dst < $ À100 nT. During extended periods without substorms, convection is driven by the MDXL to intensify the ring current of min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Another way to look at this is to calculate the total PV 5/3 contained in the ring current region. Kan et al [2007] proposed to estimate the flux integral of the entropy function that is required to support a storm time ring current. They define…”
Section: Results From 20 Idealized Stormsmentioning
confidence: 99%
“…Another way to look at this is to calculate the total PV 5/3 contained in the ring current region. Kan et al [2007] proposed to estimate the flux integral of the entropy function that is required to support a storm time ring current. They define…”
Section: Results From 20 Idealized Stormsmentioning
confidence: 99%
“…Adiabatic acceleration of the particles in the flux tube provides the population for the ring current. Kan et al [2007] discussed this issue and suggested that magnetic storm intensity might be related to the position of the neutral line in the tail during storm time substorms. Storm time substorms whose neutral line form closer to the Earth would produce a greater enhancement of the ring current as compared to storm time substorms whose neutral line forms further from the Earth.…”
Section: Generation Of the Ring Current And Resolution Of The Paradoxmentioning
confidence: 99%
“…Even though some of these increases in magnetospheric activity might involve some changes in the amount of open flux in the tail [ Boudouridis et al , 2005], the loading/unloading pattern of substorms is not evident. Thus we consider the supposition of Kan et al [2007] that the position of “substorm” neutral line is important to be only partially correct, since simulations of the storm time magnetotail do not show the loading‐unloading behavior of substorms, and in fact the term “storm time substorm” may be a misnomer. Also, it is relevant to note that Bargatze et al [1985] found that when was VB s large, the loading‐unloading response in the AE data disappeared, leaving only the directly driven response.…”
Section: Generation Of the Ring Current And Resolution Of The Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…During substorm expansion phase, sunward convection in the plasma sheet is enhanced primarily by the nightside reconnection driven by the dipolarization‐induced NEXL (near‐Earth X line) as proposed by Kan [2007]. During the storm main phase, sunward convection penetrating deeper into the inner magnetosphere is also driven by dipolarization‐induced NEXL as proposed by Kan et al [2007]. Noted that the dipolarization‐induced NEXL, formed within a few minutes after dipolarization, is proposed to drive the expanding auroral bulge during substorm expansion phase [ Kan , 2007].…”
Section: Formulation Of Sw‐m‐i Coupling Model For Polar Cap Potentialmentioning
confidence: 95%